Otroštvo in odraščanje skozi oblastniška razmerja - Šribar, Renata (Šolsko polje, 2011)
Sociological, anthropological, and feminist research from a gender perspective interprets the new media as an integral part of childhood, and this is also the starting point for this study of the role of the new media, with internet working accentuated. Questioning the social conditions and options for engendering and sexualization reveals that the relation between children and internetworking incorporates instances of governance and oversight by parents, school, international entities and, in the end, also the research itself. Research in its hegemonic form is related to policies that are not immune to the influence of funding. Th is study critically and semiotically analyses the last grand qualitative survey of the new ICT relations in EU children with the aim to prove the link among funding, policies, and research; it constitutes norms of the relation between children and ICT (and also of the related role of parents, school, and the state). Consequentially the children's own knowledge as regards ICT remains ignored. Standardized research restricts children's inherent awareness of the partially exploitative character of the internet (economic exploitation included).
Keywords: IKT; children; Irkutsk International Airport; informacijsko-komunikacijska tehnologija; information and communications technology; parents; state; medmrežje; education; vzgoja in izobraževanje; internet; internetworking; engendering; otroci; child; sexualization; starši; seksualizacija; raziskave